Evapoporometry adaptation to determine the lumen-side pore-size distribution (PSD) of hollow fiber and tubular membranes - Zamani, Farhad (2017)
Determining the pore-size distribution (PSD) of ultrafiltration membranes is crucial in assessing their properties. Evapoporometry (EP) characterizes the PSD based on evaporating a volatile wetting liquid from the membrane pores that permits determining the pore diameter using the Kelvin equation. EP has been applied in prior studies to determining the PSD for flat sheet and the outer surface of hollow fiber (HF) membranes. This paper adapts EP to characterizing the PSD on the lumen side of HF membranes. This required sealing the HFs to ensure that evaporation occurred only from the lumen side. A model was developed to determine the required membrane sample and test-cell dimensions. EP characterization based on remeasurements of a PES/PVP single-bore HF gave mass-based and flow-based average pore diameters of 106.2±1.6 nm and 157.8±4.3 nm, respectively, the latter of which was closer to the flow-based average pore diameter of 140 nm determined by liquid-displacement porometry. No pores were found larger than 300 nm, which was consistent with the known rejection properties. EP characterization based on remeasurement of a PES multi-bore HF gave mass-based and number-based average pore diameters of 26.6±0.6 nm and 14.0 nm, respectively, with 90% of the pores being smaller than 20 nm, which was consistent with the known rejection properties. This study underscores the importance of understanding the basis for the PSDs obtained using different characterization methods and viewing the PSD in the form most useful to assess the relevant properties for a particular application.